The prognostic value of long noncoding RNA activated by TGF-β in digestive system cancers: A meta-analysis. Issue 30 (24th July 2020) - Duan, Houyu; Ding, Xiang; Luo, Hesheng
Abstract: Background: To systematically evaluate whether the expression level of long non-coding RNA activated by transforming growth factor-β (lncRNA-ATB) is correlated with the prognosis of digestive system cancer (DSC) patients. Methods: PubMed, Embase, Cochrane Library, Web of Science, Springerlink, Nature, and Karger databases were searched up to April 20, 2019 by 2 experienced researchers independently. The quality of studies was assessed with the Newcastle-Ottawa scale. The Review Manager 5.2 and STATA 12.0 software were used for this meta-analysis. Result: Eleven studies with 1227 DSC patients were included in the meta-analysis. Except for pancreatic cancer, high expression of lncRNA-ATB was associated with lymph node metastasis (risk ratio (RR) = 1.26, 95% confidence interval (CI): 1.12–1.42, P < .001), advanced clinical staging (RR = 1.44, 95%CI: 1.23–1.69, P < .001), reduced overall survival rate (OS) (hazard ratio (HR) = 2.33, 95%CI: 1.22–4.50, P = .01), and recurrence-free survival (RFS) (HR = 2.61, 95%CI: 1.46–4.65, P = .001) compared with low lncRNA-ATB expression in DSCs. Conclusions: High expression of lncRNA-ATB was significantly correlated with poor prognosis for most DSCs. The expression level of lncRNA-ATB could be a promising prognostic biomarker for DSC patients.